(untitled) (Huellas, 2016)
Social representations of rural areas are discussed within the context of social, economic and cultural changes operated on these areas in the Western world. Applying a comparative methodology we have analyzed the social representations of the rural sector present in students of fourth year of high school. For this purpose we chose a rural experimental centre- Requena’s IES No. 1- and to introduce a contrast, we chose other two centres: an urban one- IES San Vicente Ferrer in Valencia- and a suburban one –the Pléyade Torrente College. From the interpretation of the results of the surveys and of the students’ mental schemas, it has been shown that the location of the school is a factor which influences the social perceptions of students. The similarities and differences regarding the social practices and the lived space account for the real conceptions (experimental centre) or idyllic ones (contrast centres) about the rural areas.